Assessment of Losses in Harvesting and Threshing by Manual Method for Wheat and Maize Crop in Samastipur District, Bihar, India - Rajak, D.; Immanuel, G.; Jat, R. (International Journal of Economic Plants, 2022)
This research was conducted at Borlaug Institute of South Asia (BISA) Pusa, Bihar to assess the losses in harvesting and threshing by manual methods for wheat and maize. 5 farmers from 15 identified villages were selected from Samastipur district of Bihar for assessing harvesting and threshing losses of wheat and maize crop. A total of 75 farmers were selected for this study from Kabargama Phulhara, Ajana, Gopalpur, Maniarpur, Rampura, Ladaura, Birsingpur, Kalyanpur, Akbarpur, Pratapur, Basudevpur, Dhruvgama, Tera, Mirjapur, Samastipur. A pre-procedure for loss assessment was used to record the details of the harvesting and threshing loss practices. It was observed that the total harvesting loss in all 15 villages were 1.65% and threshing loss 2.30% and maize 1.20%, respectively. Wheat Threshing Loss was found highest at 3.35% in Mirjapur village and the lowest at 1.18% in Rampura. Maize threshing loss was found to be highest in Pratapur village by 1.66% and lowest at 0.85% in Ladaura. The threshing loss was found less in Maize as compared to the harvesting and threshing loss of wheat and Maize due to the low loss, it is because of the long-stalked cubs of corn, in which there is no settling loss. The increase in losses was probably due to delays in harvesting due to unseasonal rains and storms, when the crop was ready for harvesting in some cases and less use of technologies at the agricultural level. There is a need for training farmers while harvesting and threshing of wheat and maize to reduce the loss of grain.